A GESTÃO POR PROCESSOS E O USO DE SOLUÇÕES BUSINESS PROCESS MANAGEMENT SYSTEMS: UM ESTUDO DE CASO NUMA ORGANIZAÇÃO DE PETRÓLEO E GÁS NOS ESTADOS DA BAHIA, ESPÍRITO SANTO E RIO DE JANEIRO - Conceição, Vanderlei Menezes (2012)
This dissertation evaluates the perception of the organization on the stage and maturity of the main initiatives in the management of critical processes in an oil and gas, using a recognized technological tools for modeling and automation, based on the model BPM (Business Process Management) and the technological solutions BPMS (Business Process Management System), to contribute in improving their business results. The research was based on a questionnaire to quantify the levels of awareness of the practices and conduct of research documents the results of pilot experiments conducted in the states of Bahia, Espírito Santo and Rio de Janeiro, to apply the concepts of BPM and BPMS in automated fields, with exploration and production On Shore and Off Shore. The data were analyzed and associated with the use of statistical techniques, considering the perception of respondents and the gains achieved in quantitative pilots, with the implementation of the concept of collaborative environment, for decision making in real time, supported by advanced technologies automation, such as the type of intelligent software BPMS in the form of web portal. The results indicated that the practices of BPM and BPMS also contributed in increasing efficiency and productivity of the fields, in reducing losses and costs and increasing value of oil and gas reserves contained in these fields. The study also allowed us to conclude that the implementation of process management is not an easy path and short-term, investments in new technology are significant; ambience and cultural issues should not be overlooked. The proper use of the techniques for modeling processes and simplification of rules of business and technology for development of BPMS solutions are critical success factors for effective implementation of process management in organizations.